Optical Coherence Tomography to Assess Proximal Side Optimization Technique in Crush Stenting - Lavarra, Francesco; Tarantini, Giuseppe; Sala, Davide; Sirbu, Vasile (Frontiers in Cardiovascular Medicine, 2022)
Aim: To explore the potential intraprocedural benefits of the Proximal Side Optimization (PSO) technique by Optical Coherence Tomography (OCT). Methods: A case series of ten consecutive true bifurcation lesions with severe long pathology of long side branch (SB) were randomly assigned to be treated by standard DK Crush procedure (non-PSO group) as compared to DK Crush in PSO modification (PSO group). Data from OCT investigation before crushing of the SB Drug-Eluting Stent (DES), after crushing, after first kissing balloon inflation (KBI), and after final angiography were compared between the two groups. Results: All ten cases were successfully treated by the assigned technique. The two groups were similar in terms of indications for the procedure, bifurcation angle, and stent dimensions. As compared to the non-PSO, the PSO group showed larger proximal SB stent areas (5.8±1.8 mm2 vs 4.5±0.5 mm2; p=0.02), the larger delta between distal and proximal stent areas before crush (1.5±0.7 mm2 vs 0.6±0.5 mm2; p=0.004), larger Space of Optimal Rewiring (SOW) after Crush (5.3±1.8 mm2 vs 2.5±1.1 mm2; p=0.02). Gaps in scaffolding within the ostial segment of the Side Branch DES were found in two patients from non-PSO group. Conclusion: The DK Crush in PSO modification results in larger SB DES and SOW areas with better apposition to the vessel wall. As result the SB DES acquires a funnel shape which reduces the risk of passage outside the SB stent struts during re-wiring, allowing predictable and secure results.